Electrochemical equipment and power-using facilities including the same
By optimizing the positive electrode material and process parameters and controlling the peak position and intensity of heat generation, the shortcomings of lithium-ion batteries in terms of energy density, safety, cycle performance and life are solved, and better battery performance and stability are achieved.
Patent Information
- Application Number
- JP2023544329
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-28
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-09-28
Smart Images

Figure 0007650988000001 
Figure 0007650988000002 
Figure 0007650988000003
Abstract
Description
[Technical field]
[0001] The present invention relates to the electrochemical field, and more particularly to electrochemical devices and power-using equipment including the same. [Background technology]
[0002] Lithium ion batteries have advantages such as large energy storage density, high open circuit voltage, low self-discharge rate, long cycle life, and high safety characteristics, and are therefore widely used in various fields such as electric energy storage, portable electronic devices, electric vehicles, electric bicycles, and aerospace equipment. As portable electronic devices and electric vehicles enter a rapid development stage, the market has higher and higher requirements for the energy density, safety characteristics, cycle characteristics, and life of lithium ion batteries. Summary of the Invention
[0003] An object of the present invention is to provide an electrochemical device and power-using equipment including the same, thereby improving the cycle characteristics, rate characteristics, and safety characteristics of the electrochemical device.
[0004] A first aspect of the present invention provides an electrochemical device including a positive electrode piece, the positive electrode piece including a positive electrode active material. When the state of charge SOC of the electrochemical device is 90% to 100%, a DSC (differential scanning calorimetry) curve of the positive electrode piece has a first exothermic peak A1 and a second exothermic peak A2 between 150°C to 400°C. Here, with respect to the mass of the positive electrode active material, the first exothermic peak A1 is an exothermic peak having a peak intensity of more than 0.1 mW / mg closest to 400°C, the second exothermic peak A2 is an exothermic peak having a peak intensity of more than 0.1 mW / mg closest to 150°C, and the difference between the peak position Ta of the first exothermic peak A1 and the peak position Tb of the second exothermic peak A2 is 20°C to 150°C. As can be understood, the exothermic peak includes an exothermic peak formed by the cooperation of the interface protective film and the positive electrode active material itself, that is, the peak position Ta and peak intensity of the first exothermic peak A1 and the peak position Tb and peak intensity of the second exothermic peak A2 are determined by both the interface protective film and the positive electrode active material. Without being limited to any theory, the peak intensity of the second exothermic peak A2 is more than 0.1 mW / mg relative to the mass of the positive electrode active material, and the difference between the peak position Ta of the first exothermic peak A1 closest to 400°C and the peak position Tb of the second exothermic peak A2 closest to 150°C is 20°C to 150°C. This indicates that the difference in peak position between the exothermic peaks formed by the cooperation of the interface protective film and the positive electrode active material is small, and the thermal stability at the interface between the positive electrode active material and the electrolyte is high and not easily destroyed at high temperatures, thereby better protecting the surface of the positive electrode active material, suppressing the occurrence of side reactions, and improving the stability of the positive electrode active material. At the same time, the peak intensity of the second exothermic peak A2 is more than 0.1 mW / mg relative to the mass of the positive active material, so that the positive active material has a sufficient protective film on its surface, which effectively improves the thermal stability of the electrochemical device, and thus the electrochemical device has good cycle performance, rate performance and safety performance.
[0005] In the present invention, when the positive electrode pieces adopt the same positive electrode active material, the peak position, peak intensity, and the difference between the peak position Ta of the first exothermic peak A1 and the peak position Tb of the second exothermic peak A2 are controlled within the range of the present invention by adjusting the injection coefficient, the formation upper limit voltage after the electrochemical device is packaged, the formation temperature, the formation standing time, etc., thereby achieving the object of the present invention, and the electrochemical device has good cycle characteristics, rate characteristics, and safety characteristics. The present invention is not particularly limited in the specific range of the injection coefficient, the formation upper limit voltage after the electrochemical device is packaged, the formation temperature, and the formation standing time, as long as the object of the present invention can be achieved.
[0006] In one embodiment of the present invention, the peak position Ta of the first exothermic peak A1 is located at 250° C. to 400° C., and the peak position Tb of the second exothermic peak A2 is located at 200° C. to 300° C. In this manner, by increasing the peak positions of both the first exothermic peak A1 and the second exothermic peak A2, the thermal stability of the positive electrode active material and its surface protective film is improved.
[0007] In one embodiment of the present invention, the ratio S of the peak intensity of the first exothermic peak A1 to the peak intensity of the second exothermic peak A2 is 0.1 to 10. For example, the ratio S of the peak intensity of the first exothermic peak A1 to the peak intensity of the second exothermic peak A2 may be 0.1, 0.7, 1.2, 1.4, 1.5, 6.1, 9.8, 10, or any one value between any two of the above numerical ranges. Furthermore, the ratio S of the peak intensity of the first exothermic peak A1 to the peak intensity of the second exothermic peak A2 is 0.7 to 10. Without being limited to any theory, by controlling the ratio S of the peak intensity of the first exothermic peak A1 to the peak intensity of the second exothermic peak A2 within the above range, the difference in stability between the positive electrode active material and its surface protective film can be reduced, which is further advantageous in improving the cycle characteristics and rate characteristics of the electrochemical device.
[0008] In one embodiment of the present invention, the positive electrode pieces are immersed in N-methylpyrrolidone (NMP) at 25°C for 8h, and then the N-methylpyrrolidone is replaced with the same compounding ratio and immersed twice. After that, the DSC curve of the positive electrode pieces has an exothermic peak B between 240°C and 400°C, and the peak area of the exothermic peak B is less than 360 J / g relative to the mass of the positive electrode active material. Each time the positive electrode pieces are immersed in NMP, the volume ratio of the positive electrode pieces to NMP is 1:10 to 1:20. After the positive electrode pieces are immersed in NMP three times, most or all of the protective film on the surface of the positive electrode active material is washed out, so that the peak position Tc of the exothermic peak B is mainly determined by the positive electrode active material. The peak position Tc of exothermic peak B is in the range of 240°C to 400°C, and the peak area of exothermic peak B relative to the mass of the positive electrode active material is less than 360 J / g, which indicates that the thermal stability of the positive electrode active material is high. Thus, the electrochemical device has high thermal stability and therefore good safety characteristics.
[0009] In one embodiment of the present invention, the positive electrode active material comprises a lithium transition metal composite oxide, the lithium transition metal composite oxide comprises a doping element M, the doping element M comprises at least one of Al, Mg, Ti, Cr, Cu, Fe, Co, W, Zn, Ga, Zr, Ru, Ag, Sn, Au, La, Ce, Pr, Nd, Sm, Nb, and Gd. The lithium transition metal composite oxide further comprises Mn. The selection of the doping element is further advantageous in improving the cycle characteristics and rate characteristics of the electrochemical device.
[0010] Furthermore, the molar ratio n of the doping element M to Mn M / n Mn For example, the molar ratio n of the doping element M to Mn is 0.1% to 10%. M / n Mn may be 0.1%, 2%, 4%, 6%, 9%, 10%, or any one value between any two of the above values. Without being limited to any theory, the molar ratio n of the doping element M to Mn M / n Mn Controlling within the above range is advantageous in improving the cycle characteristics and rate characteristics of the electrochemical device.
[0011] Furthermore, the positive electrode active material contains Li x Mn y M z O4, where 0.6 ≦ x ≦ 1.2, 0.8 ≦ y ≦ 1, 0 < z ≦ 0.2, and M contains at least one of Al, Mg, Ti, Cr, Cu, Fe, Co, W, Zn, Ga, Zr, Ru, Ag, Sn, Au, La, Ce, Pr, Nd, Sm, Nb, and Gd.
[0012] Preferably, the positive electrode active material is LiMn 1.96 Al 0.04 O4, LiMn 1.96 Mg 0.04 O4, LiMn 1.92 Al 0.04 Mg 0.04 O4, LiMn 1.88 Al 0.04 Mg 0.04 Nb 0.04 O4, LiMn 1.88 Al 0.08 Nb 0.04 O4, LiMn 1.84 Al 0.12 Nb 0.04 O4, LiMn 1.84 Al 0.16 O4, and LiMn 1.88 Al 0.08 Nb 0.04 O4, etc.
[0013] In one embodiment of the present invention, the doping element M contains at least one of Al and Nb, and by adding the doping element M to the positive electrode active material, the electrochemical device is made to have excellent cycle characteristics and rate characteristics.
[0014] Furthermore, the molar ratio n (Al+Nb) / n Mn of the total molar amount of Al and Nb to Mn is 1% to 10%. For example, the molar ratio n (Al+Nb) / n Mnmay be 1%, 2%, 4%, 6%, 9%, 10%, or any one value between any two of the above values. Without being limited to any theory, the molar ratio n (Al+Nb) / n Mn Controlling within the above range is advantageous in improving the cycle characteristics and rate characteristics of the electrochemical device.
[0015] In one embodiment of the present invention, the positive electrode active material includes secondary particles formed by aggregation of primary particles, and the average particle diameter Ds of the primary particles is 0.8 μm to 5 μm. For example, the average particle diameter Ds of the primary particles may be 0.8 μm, 1.2 μm, 2.4 μm, 4.3 μm, 5 μm, or any one value between any two of the above numerical ranges. Without being limited by any theory, if the average particle diameter Ds of the primary particles is too small, there are too many active sites, and side reactions that affect the performance of the electrochemical device increase. If the average particle diameter Ds of the primary particles is too large, the contact between the positive electrode active material and the electrolyte is limited, which affects the performance of the electrochemical device. Controlling the average particle diameter Ds of the positive electrode active material primary particles within the above range is more advantageous in improving the cycle characteristics and rate characteristics of the electrochemical device.
[0016] In one embodiment of the present invention, the average particle diameter Dv50 of the positive electrode active material is 5 μm to 15 μm. For example, the average particle diameter Dv50 of the positive electrode active material may be 5 μm, 6.9 μm, 8.4 μm, 8.7 μm, 10.3 μm, 12.4 μm, 12.6 μm, or any one of the ranges between any two of the above values.
[0017] In one embodiment of the present invention, the ratio Dv50 / Ds of the average particle diameter Dv50 of the positive electrode active material to the average particle diameter Ds of the primary particles is 1.5 to 20. For example, the ratio Dv50 / Ds of the average particle diameter Dv50 of the positive electrode active material to the average particle diameter Ds of the primary particles may be 1.5, 1.6, 3.6, 8.6, 10.5, 15.4, 15.5, or any one of the ranges between any two of the above numerical values.
[0018] In one embodiment of the present invention, the positive electrode active material has a spinel structure, and the unit lattice parameter a of the positive electrode active material is 0.8200 nm to 0.8250 nm. For example, the unit lattice parameter a of the positive electrode active material may be 0.8200 nm, 0.8204 nm, 0.8214 nm, 0.8217 nm, 0.8220 nm, 0.8226 nm, 0.158 nm, 0.8232 nm, 0.8233 nm, 0.8234 nm, 0.8239 nm, 0.8250 nm, or any one value between any two of the above numerical ranges. Without being limited to any theory, controlling the unit lattice parameter a of the positive electrode active material within the above range is more advantageous for exhibiting capacity, and more advantageous for improving the cycle characteristics and rate characteristics of the electrochemical device.
[0019] In one embodiment of the present invention, the electrochemical device further includes an electrolyte, and the electrolyte includes an unsaturated carbonate ester compound. By adding the unsaturated carbonate ester compound to the electrolyte, a stable solid electrolyte interface (SEI) film can be formed on the negative electrode surface, which improves the dissolution of Mn from the positive electrode active material and improves the cycle characteristics of the electrochemical device.
[0020] In one embodiment of the present invention, the unsaturated carbonate compound includes a compound represented by formula (I). [ka] In formula (I), R 3 is selected from a substituted C1-C6 alkylene group, a substituted or unsubstituted C2-C6, and when substituted, the substituents include at least one of a halogen atom, a C1-C6 alkyl group, and a C2-C6 alkenyl group; and R 3 When is selected from substituted C1-C6 alkylene groups, the substituents include at least a C2-C6 alkenyl group.
[0021] Preferably, the unsaturated carbonate compound is selected from at least one of the following compounds (I-1) to (I-8). [ka]
[0022] In one embodiment of the present invention, the mass fraction of the unsaturated carbonate ester compound is 0.01% to 5% with respect to the mass of the electrolyte. For example, the mass fraction of the unsaturated carbonate ester compound may be 0.01%, 0.05%, 1%, 2%, 3%, 4%, 5%, or any one value between any two of the above numerical ranges. Without being limited to any theory, if the mass fraction of the unsaturated carbonate ester compound is too small, the effect of forming an SEI film on the negative electrode to improve the cycle characteristics of the electrochemical device is not clear. If the mass fraction of the unsaturated carbonate ester compound is too high, the SEI film formed on the negative electrode is too thick, which increases the impedance and reduces the rate characteristics. Therefore, controlling the mass fraction of the unsaturated carbonate ester compound within the above range is advantageous in improving the cycle characteristics and rate characteristics of the electrochemical device.
[0023] The electrolyte of the present invention further includes a lithium salt and a non-aqueous solvent. The present invention is not particularly limited to the type of lithium salt, as long as the object of the present invention can be achieved. For example, the lithium salt may include at least one of lithium hexafluorophosphate (LiPF6), LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, and LiSiF6. Since LiPF6 provides high ionic conductivity and can improve the cycle characteristics of a lithium ion battery, it is preferable to include LiPF6. The present invention is not particularly limited to the non-aqueous solvent, as long as the object of the present invention can be achieved. For example, the non-aqueous solvent may include at least one of a carbonate ester compound, a carboxylate ester compound, an ether compound, and another organic solvent. The carbonate ester compound may be at least one of a chain carbonate ester compound and a cyclic ester compound. The chain carbonate ester compound may include at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), and methyl ethyl carbonate (MEC). The cyclic carbonate ester compound may include at least one of ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC). The carboxylic acid ester compound may include at least one of ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, and propyl propionate. The ether compound may include at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, and tetrahydrofuran.The other organic solvent may include at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphate esters.
[0024] The positive electrode piece of the present invention is not particularly limited, and may be any one that can achieve the object of the present invention. For example, the positive electrode piece includes a positive electrode collector and a positive electrode material layer. The positive electrode collector of the present invention is not particularly limited, and may be any one that can achieve the object of the present invention. For example, the positive electrode collector may include an aluminum foil, an aluminum alloy foil, and a composite current collector. The positive electrode material layer of the present invention includes a positive electrode active material described in any one of the above technical forms of the present invention. In the present invention, the thickness of the positive electrode collector and the positive electrode material layer is not particularly limited, and may be any one that can achieve the object of the present invention. For example, the thickness of the positive electrode collector is 5 μm to 20 μm, preferably 6 μm to 18 μm. The thickness of the positive electrode material layer on one side is 30 μm to 120 μm. In the present invention, the positive electrode material layer may be installed on one surface in the thickness direction of the positive electrode collector, or may be installed on two surfaces in the thickness direction of the positive electrode collector. Here, the "surface" may be the entire area of the positive electrode current collector or a part of the area of the positive electrode current collector, and the present invention is not particularly limited as long as the object of the present invention can be achieved. Optionally, the positive electrode piece further includes a conductive layer, and the conductive layer is located between the positive electrode current collector and the positive electrode material layer. The composition of the conductive layer is not particularly limited, and may be a common conductive layer in the art. For example, the conductive layer includes a conductive agent and a binder.
[0025] The electrochemical device of the present invention further includes a negative electrode sheet. The present invention has no particular limitation on the negative electrode sheet, as long as the object of the present invention can be achieved. For example, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer. The negative electrode current collector of the present invention has no particular limitation, as long as the object of the present invention can be achieved. For example, the negative electrode current collector may include a copper foil, a copper alloy foil, a nickel foil, a stainless steel foil, a titanium foil, a foamed nickel, a foamed copper, or a composite current collector, etc. The negative electrode material layer of the present invention contains a negative electrode active material. The present invention has no particular limitation on the type of the negative electrode active material, as long as the object of the present invention can be achieved. For example, the negative electrode active material may include at least one of natural graphite, artificial graphite, mesocarbon microbeads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO x (0 < x < 2), Li-Sn alloy, Li-SN-O alloy, Sn, SnO, SnO2, lithium titanate with a spinel structure Li4Ti5O 12 , Li-Al alloy, or metallic lithium. In the present invention, the thicknesses of the negative electrode current collector and the negative electrode material layer have no particular limitation, as long as the object of the present invention can be achieved. For example, the thickness of the negative electrode current collector is 6 μm to 10 μm, and the thickness of the negative electrode material layer on one side is 30 μm to 130 μm. In the present invention, the negative electrode material layer may be disposed on one surface in the thickness direction of the negative electrode current collector, or may be disposed on two surfaces in the thickness direction of the negative electrode current collector. Here, the "surface" may be the entire region of the negative electrode current collector, or may be a part of the region of the negative electrode current collector. The present invention has no particular limitation, as long as the object of the present invention can be achieved. Optionally, the negative electrode sheet further includes a conductive layer, and the conductive layer is located between the negative electrode current collector and the negative electrode material layer. The composition of the conductive layer has no particular limitation, and it may be a general conductive layer in this field. The conductive layer includes a conductive agent and a binder.
[0026] The conductive agent is not particularly limited as long as it can achieve the object of the present invention. For example, the conductive agent may include at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon nanofibers, graphite, acetylene black, carbon black, ketjen black, carbon quantum dots, and graphene. For example, the binder may include at least one of polypropylene alcohol, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyamide-imide, styrene butadiene rubber (SBR), polyvinyl alcohol (PVA), polyvinylidene fluoride, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), aqueous acrylic resin, carboxymethyl cellulose (CMC), and sodium carboxymethyl cellulose (CMC-Na).
[0027] The electrochemical device of the present invention further includes a separator for separating the positive electrode pieces from the negative electrode pieces, preventing internal short circuit of the lithium ion battery, allowing the electrolyte ions to pass freely, and completing the electrochemical charge and discharge process. The separator in the present invention is not particularly limited as long as it can achieve the object of the present invention. For example, it is at least one of polyolefin (PO) separators mainly made of polyethylene (PE) and polypropylene (PP), polyester film (e.g., polyethylene terephthalate (PET) film), cellulose film, polyimide film (PI), polyamide film (PA), spandex, aramid film, woven film, nonwoven film (nonwoven fabric), microporous film, composite film, separator paper, compressed film, and spun film. For example, the separator may include a substrate layer and a surface treatment layer. The substrate layer may be a nonwoven fabric, film, or composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate, and polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite film can be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or may be a layer made by mixing a polymer and an inorganic material. For example, the inorganic material layer includes inorganic particles and a binder, and the inorganic particles are not particularly limited and are, for example, selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium oxide, tin oxide, cerium oxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate.The binder is not particularly limited, and may be selected from at least one of polyvinylidene fluoride, copolymers of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylic acid ester, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene. The polymer layer includes a polymer, and the polymer material includes at least one of polyamide, polyacrylonitrile, acrylic acid ester polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).
[0028] The electrochemical device of the present invention is not particularly limited and may include any device that performs an electrochemical reaction. In some embodiments, the electrochemical device may include, but is not limited to, a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0029] The process of preparing an electrochemical device is well known to those skilled in the art, and the present invention is not particularly limited, and may include, for example, stacking a positive electrode piece, a separator, and a negative electrode piece in order, and if necessary, winding, folding, or other operations to obtain a wound electrode assembly, placing the electrode assembly in an outer case, injecting an electrolyte into the outer case and sealing it to obtain an electrochemical device, or stacking a positive electrode piece, a separator, and a negative electrode piece in order, fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly in a stacked structure, placing the electrode assembly in an outer case, injecting an electrolyte into the outer case and sealing it to obtain an electrochemical device, but is not limited thereto. In addition, if necessary, an overcurrent protection element, a lead plate, etc. can be placed in the outer case to prevent an increase in pressure inside the electrochemical device and overcharging and discharging.
[0030] A second aspect of the present invention provides an electric power consumption facility including the electrochemical device according to any one of the above-described embodiments, the electric power consumption facility having good cycle characteristics, rate characteristics and safety characteristics.
[0031] The power-using equipment of the present invention is not particularly limited, and may include, but is not limited to, notebook computers, pen-input computers, mobile computers, electronic book players, mobile phones, portable facsimiles, portable copiers, portable printers, stereo headsets, video recorders, LCD televisions, portable cleaners, portable CD players, minidiscs, walkie-talkies, electronic notebooks, calculators, memory cards, portable tape recorders, radios, backup power supplies, motors, automobiles, motorcycles, power-assisted bicycles, bicycles, lighting equipment, toys, game consoles, watches, power tools, flashlights, cameras, large household batteries, and lithium ion capacitors.
[0032] The present invention provides an electrochemical device and a power-using equipment including the electrochemical device. The electrochemical device includes a positive electrode piece, and the positive electrode piece includes a positive electrode active material. When the state of charge SOC of the electrochemical device is 90% to 100%, the DSC curve of the positive electrode piece has a first exothermic peak A1 and a second exothermic peak A2 between 150°C to 400°C, and the first exothermic peak A1 is an exothermic peak having a peak intensity of more than 0.1 mW / mg closest to 400°C, and the second exothermic peak A2 is an exothermic peak having a peak intensity of more than 0.1 mW / mg closest to 150°C, and the difference between the peak position Ta of the first exothermic peak A1 and the peak position Tb of the second exothermic peak A2 is 20°C to 150°C, relative to the mass of the positive electrode active material. The electrochemical device has good cycle characteristics, rate characteristics, and safety characteristics. The electronic equipment including the electrochemical device also has good cycle characteristics, rate characteristics, and safety characteristics. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0033] In order to make the objectives, technical solutions and advantages of the present invention clearer, the present invention will be described in more detail with reference to the drawings and embodiments. Obviously, the described embodiments are not all the embodiments, but are merely some of the embodiments of the present invention. Any other technical solutions obtained by those skilled in the art based on the embodiments of the present invention are within the protection scope of the present invention.
[0034] In the specific embodiment of the present invention, the present invention will be described using a lithium ion battery as an example of an electrochemical device, but the electrochemical device of the present invention is not limited to a lithium ion battery.
[0035] Hereinafter, the embodiments of the present invention will be described in more detail with reference to examples and comparative examples. Various tests and evaluations were carried out according to the following methods. In addition, "parts" and "%" are by mass unless otherwise specified.
[0036] Measurement method and equipment DSC measurements DSC was used to measure the relationship between the heat flow difference and temperature between the sample and the reference. The DSC curve was measured using a synchronous thermal analyzer of STA4493F3 type. As a method, a lithium-ion battery was charged to 100% SOC, disassembled, and then the positive electrode piece was taken out and cut into a standard size of 10 cm x 10 cm. The measurement temperature range was 150 ° C to 400 ° C, and the heating rate was 10 ° C / min, and the DSC curve was obtained.
[0037] Measurement of the content of each element in the positive electrode active material A lithium-ion battery is discharged to 2.8 V and disassembled, after which the positive electrode piece is removed and washed three times with high-purity anhydrous DMC, immersed for 8 hours each time, and then placed in a vacuum drying oven for 12 hours. The positive electrode active material is then scraped off from the positive electrode piece, after which measurements are taken using an inductively coupled plasma spectrometer (ICP) or the like.
[0038] Measurement of the average particle size Ds of primary particles The average particle diameter Ds of the primary particles of the positive electrode active material was measured using a scanning electron microscope, and the positive electrode material was photographed using a scanning electron microscope (ZEISS Sigma-02-33, Germany). Then, 200 primary particles of the positive electrode active material that were completely shaped and not blocked in the electron microscope image were randomly selected, and the average value of the longest diameter in the microscope image of the primary particles was recorded as the average particle diameter Ds.
[0039] Measurement of average particle size Dv50 The measurements were made using a Mastersizer 3000 laser particle size analyzer. Laser particle size measurement is based on the mechanism that different sizes of particles can cause different intensities of scattering in a laser. Dv50 is the particle size at which the cumulative volume from the small particle size side reaches 50% in the volume-based particle size distribution.
[0040] Calculating the filling factor Filling factor = electrolyte capacity / Li-ion battery capacity.
[0041] Measurement of high temperature capacity retention rate At 45°C, the lithium-ion battery was charged to 4.2V at a constant current of 0.5C, and finally charged at a constant voltage until the current reached 0.05C, and the charge capacity of the first cycle was recorded. It was then discharged to 3.0V at a constant current of 1C, and the discharge capacity of the first cycle was recorded. Next, 500 charge-discharge cycles were performed using the same steps, and the discharge capacity of the 500th cycle was recorded. The capacity retention rate was used as an index to evaluate the cycle characteristics of the lithium-ion battery. Capacity retention rate = (discharge capacity at 500th cycle / initial discharge capacity) x 100%.
[0042] Rate characteristic measurement At 25°C, the lithium-ion secondary battery was charged at a constant current of 0.2C up to 4.2V, then charged at a constant voltage of 0.05C, left to stand for 30 minutes, and then discharged at a constant current of 0.2C up to 3.0V, and the discharge capacity of the lithium-ion battery at a rate of 0.2C was measured.
[0043] At 25°C, the lithium-ion secondary battery was charged at a constant current of 0.2C up to 4.2V, then further charged at a constant voltage until the current fell to 0.05C or less, then left to stand for 30 minutes, and further discharged at a constant current of 1C up to 3.0V, and the discharge capacity of the lithium-ion secondary battery at a rate of 1C was measured.
[0044] Lithium-ion battery discharge capacity retention rate (%) at 1C rate = discharge capacity at 1C rate / discharge capacity at 0.2C rate × 100%.
[0045] Example 1-1 <Preparation of positive electrode piece> The positive electrode active material LiMn 1.96 Al 0.04 O4, acetylene black as a conductive agent, and polyvinylidene fluoride (PVDF) as a binder were mixed in a weight ratio of 96:2:2, and NMP was added as a solvent to prepare a slurry with a solid content of 75%, and the system was stirred with a vacuum stirrer until it became a uniform positive electrode slurry. The positive electrode slurry was uniformly applied to one side of the aluminum foil of a positive electrode current collector with a thickness of 10 μm, and dried under a condition of 90 ° C., to obtain a positive electrode piece with a coating thickness of 110 m and a positive electrode material applied on one side. Then, the above steps were repeated on the other surface of the positive electrode piece to obtain a positive electrode piece with a positive electrode material applied on both sides. After the coating was completed, the positive electrode piece was cut to a standard of 74 mm × 867 mm and prepared for the next step. Here, the Ds of the positive electrode active material was 0.8 μm, the Dv50 was 12.4 μm, and the unit lattice parameter a of the positive electrode active material was 0.8220 nm.
[0046] <Preparation of negative electrode piece> Graphite, which is the negative electrode active material, SBR, which is the binder, and sodium carboxymethylcellulose, which is the thickener, were mixed in a weight ratio of 97.5:1.5:1, and deionized water was added as a solvent to prepare a negative electrode slurry with a solid content of 70%, which was then stirred with a vacuum stirrer until the system became a uniform negative electrode slurry. The negative electrode slurry was evenly applied to one side of the copper foil of a negative electrode current collector with a thickness of 8 m, and dried at 90 ° C to obtain a negative electrode piece with a coating thickness of 130 m on one side. The above steps were then repeated on the other surface of the negative electrode to obtain a negative electrode piece with a negative electrode material applied on both sides. After coating was completed, the negative electrode piece was cut to a standard of 76 mm x 851 mm and prepared for the next step.
[0047] <Preparation of separator> The separator used was a porous polyethylene substrate with a ceramic coating applied to both sides.
[0048] <Preparation of electrolyte> In a glove box with an argon gas atmosphere with a water content of less than 10 ppm, ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), and propyl propionate (PP) were mixed uniformly in a mass ratio of 20:30:20:30 to obtain an organic solvent. Vinylene carbonate (VC) and lithium salt LiPF6 were added to the organic solvent and mixed uniformly to obtain an electrolyte. Here, the concentration of LiPF6 was 1.15 mol / L, and the mass fraction of VC was 0.05% relative to the mass of the electrolyte.
[0049] <Making a lithium-ion battery> The positive electrode piece, separator, and negative electrode piece prepared above were stacked in order, and the separator was placed between the positive electrode piece and the negative electrode piece to play the role of isolation, and then wound to obtain an electrode assembly. The electrode assembly was placed in an aluminum plastic film exterior case, and placed in a vacuum drying oven at 85°C for 12 hours to remove moisture, and the above-prepared electrolyte was injected, and a lithium-ion battery was obtained through processes such as vacuum packaging, standing, formation, and shaping. Here, the injection coefficient was 4.55g / Ah, the formation upper limit voltage after packaging was 4.12V, the formation temperature was 85°C, and the formation treatment time was 2.3h.
[0050] Example 1-2 was the same as Example 1-1, except that in <Preparation of electrolyte>, the mass fraction of VC was 1% relative to the mass of the electrolyte, and in <Preparation of lithium ion battery>, the formation upper limit voltage after packaging was 4.15 V, the formation temperature was 88° C., and the formation rest time was 2.7 h.
[0051] In Example 1-3, in <Preparation of lithium ion battery>, the formation upper limit voltage after packaging was 4.18 V, the formation temperature was 90° C., and the formation rest time was 3.0 h, except that it was the same as Example 1-2.
[0052] In Example 1-4, in <Preparation of lithium ion battery>, the formation upper limit voltage after packaging was 4.21 V, the formation temperature was 93° C., and the formation rest time was 3.4 h, except that it was the same as Example 1-2.
[0053] Example 1-5 was the same as Example 1-1, except that in <Preparation of electrolyte>, the mass fraction of VC was 5% relative to the mass of the electrolyte, and in <Preparation of lithium ion battery>, the injection coefficient was 4.35 g / Ah.
[0054] Example 1-6 was the same as Example 1-1, except that in <Preparation of electrolyte>, the mass fraction of VC was 3% relative to the mass of the electrolyte, and in <Preparation of lithium ion battery>, the injection coefficient was 4.15 g / Ah.
[0055] In Examples 2-1 to 2-12, in <Preparation of electrolyte solution>, the mass fraction of VC is 1% relative to the mass of the electrolyte solution, and the type of positive electrode active material, n M / n Mn , n (Al+Nb) / n Mn The results were the same as in Example 1-1, except that the unit cell parameter a was adjusted.
[0056] Examples 3-1 to 3-7 were similar to Example 2-4, except that Ds, Dv50, Dv50 / Ds, and unit cell parameter a were adjusted according to Table 3.
[0057] In Example 4-1, in <Preparation of Positive Electrode Pieces>, the positive electrode active material was LiMn 1.88 Al 0.08 Nb 0.04 O4, Ds was 2.4 μm, Dv50 was 8.7 μm, and the unit cell parameter a was 0.8232 nm. In the <Preparation of electrolyte>, 4,5-dimethyl-1,3-dioxol-2-one (DMDO) (I-6) was used instead of VC, and the mass fraction of 4,5-dimethyl-1,3-dioxol-2-one was 1% relative to the mass of the electrolyte. In the <Preparation of lithium ion battery>, the injection coefficient was 4.53 g / Ah, the formation upper limit voltage after packaging was 4.13 V, the formation temperature was 86° C., and the formation rest time was 2.3 h. Except for this, the same as in Example 1-1.
[0058] Example 4-2 was the same as Example 4-1 except that in <Preparation of electrolyte>, a combination of 4,5-dimethyl-1,3-dioxol-2-one and VC was used, and the mass fraction of 4,5-dimethyl-1,3-dioxol-2-one (DMDO) was 1% and the mass fraction of VC was 1% relative to the mass of the electrolyte, and in <Preparation of lithium ion battery>, the injection coefficient was 4.57g / Ah, the formation upper limit voltage after packaging was 4.15V, the formation temperature was 88°C, and the formation rest time was 2.3h.
[0059] In Example 4-3, in <Preparation of Positive Electrode Pieces>, the positive electrode active material was LiMn 1.84 Al 0.16 O4, Ds was 2.4 μm, Dv50 was 8.7 μm, the unit lattice parameter a was 0.8214 nm, in <Preparation of electrolyte>, the mass fraction of VC was 2% relative to the mass of the electrolyte, in <Preparation of lithium ion battery>, the injection coefficient was 4.6 g / Ah, the formation upper limit voltage after packaging was 4.2 V, the formation temperature was 88° C., and the formation rest time was 2.5 h.
[0060] Example 4-4 was the same as Example 4-3, except that in <Preparation of Electrolyte Solution>, the mass fraction of VC was 4% with respect to the mass of the electrolyte solution.
[0061] Comparative Example 1 was similar to Example 1-1, except that in <Preparation of electrolyte>, the mass fraction of VC was 4% relative to the mass of the electrolyte, and in <Preparation of lithium ion battery>, the injection coefficient was 4.06 g / Ah, the formation upper limit voltage after packaging was 4.20 V, and the formation temperature was 88° C.
[0062] The fabrication parameters and performance parameters related to Examples 1-1 to 1-6 and Comparative Example 1 are shown in Table 1, the fabrication parameters and performance parameters related to Examples 2-1 to 2-12 are shown in Table 2, the fabrication parameters and performance parameters related to Examples 3-1 to 3-7 are shown in Table 3, and the fabrication parameters and performance parameters related to Examples 4-1 to 4-4 are shown in Table 4.
[0063] [Table 1]
[0064] As can be seen from Examples 1-1 to 1-6 and Comparative Example 1, the rate characteristics and cycle characteristics (capacity retention rate) of the lithium ion battery changed with the change in the peak position Ta and peak intensity of the first exothermic peak A1 and the peak position Tb and peak intensity of the second exothermic peak A2. By adopting a lithium ion battery in which the peak intensity of the second exothermic peak A2 was more than 0.1 mW / mg and the difference between the peak position Ta of the first exothermic peak A1 and the peak position Tb of the second exothermic peak A2 was within the range of the present invention, the rate characteristics and cycle characteristics were improved.
[0065] [Table 2]
[0066] Note: In Table 2, "\" indicates that there is no corresponding parameter.
[0067] [Table 3]
[0068] [Table 4]
[0069] As can be seen from the comparison of Examples 2-1 to 2-12, compared with Example 2-1 in which only Mg was doped, Examples 2-2 to 2-12 in which Al and / or Nb were doped can remarkably improve the cycle characteristics of the lithium ion battery, and the type of the positive electrode active material, the molar ratio n of the doping element M to Mn, M / n Mn , the molar ratio n of the sum of the molar amounts of Al and Nb to Mn (Al+Nb) / n Mn As long as the unit lattice parameter a of the positive electrode active material is within the range of the present invention, the lithium ion battery can have good rate characteristics and cycle characteristics.
[0070] As can be seen from Examples 3-1 to 3-7, the examples in which the average particle diameter Ds of the primary particles of the positive electrode active material is 0.8 μm to 5 μm, the average particle diameter Dv50 of the positive electrode active material is 5 μm to 15 μm, and Dv50 / Ds is in the range of 1.5 to 20 can simultaneously have excellent rate characteristics and cycle characteristics.
[0071] As can be seen from Examples 4-1 to 4-4, by selecting different types of unsaturated carbonate ester compounds and their contents and adjusting the injection coefficient and formation conditions, it is possible to achieve lithium ion batteries having good rate characteristics and cycle characteristics.
[0072] The above are merely relatively preferred embodiments of the present invention, and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention are all within the protection scope of the present invention.
Claims
1. 1. An electrochemical device comprising a positive electrode strip and an electrolyte, The positive electrode piece includes a positive electrode active material, When the state of charge SOC of the electrochemical device is 90% to 100%, a DSC curve of the positive electrode piece has a first exothermic peak A1 and a second exothermic peak A2 between 150° C. to 400° C., and relative to the mass of the positive electrode active material, the first exothermic peak A1 is an exothermic peak having a peak intensity of more than 0.1 mW / mg closest to 400° C. and the second exothermic peak A2 is an exothermic peak having a peak intensity of more than 0.1 mW / mg closest to 150° C., and a difference between a peak position Ta of the first exothermic peak A1 and a peak position Tb of the second exothermic peak A2 is 20° C. to 150° C., The positive electrode active material has a spinel structure, The positive electrode active material includes a lithium transition metal composite oxide, and the lithium transition metal composite oxide includes a doping element M, and the doping element M includes at least one of Al, Mg, Ti, Cr, Cu, Fe, Co, W, Zn, Ga, Zr, Ru, Ag, Sn, Au, La, Ce, Pr, Nd, Sm, Nb, and Gd; The lithium transition metal composite oxide further contains Mn, and the molar ratio n M / n Mn of the doping element M to Mn is 0.1% to 10%; The electrolyte contains an unsaturated carbonate compound, The DSC curve is obtained under the conditions of a measurement temperature range of 150° C. to 400° C. and a temperature rise rate of 10° C. / min.
2. 2. The electrochemical device according to claim 1, wherein the first exothermic peak A1 has a peak position Ta located at 250°C to 400°C, and the second exothermic peak A2 has a peak position Tb located at 200°C to 300°C.
3. 2. The electrochemical device according to claim 1, wherein a ratio S of a peak intensity of the first exothermic peak A1 to a peak intensity of the second exothermic peak A2 is 0.1 to 10.
4. 2. The electrochemical device according to claim 1, wherein the positive electrode pieces are immersed in N-methylpyrrolidone at 25° C. for 8 hours, the N-methylpyrrolidone is replaced, and the positive electrode pieces are immersed twice. After this, the DSC curve of the positive electrode pieces has an exothermic peak B between 240° C. and 400° C., and the peak area of the exothermic peak B is less than 360 J / g relative to the mass of the positive electrode active material.
5. The doping element M contains at least one of Al and Nb, and the molar ratio n of the sum of the molar amounts of Al and Nb to Mn is (Al+Nb) / n Mn The electrochemical device of claim 1 , wherein is between 1% and 10%.
6. The positive electrode active material includes secondary particles formed by aggregation of primary particles, and the electrochemical device includes: a) the average particle diameter Ds of the primary particles is 0.8 μm to 5 μm; b) the average particle diameter Dv50 of the positive electrode active material is 5 μm to 15 μm; c) the ratio Dv50 / Ds of the average particle diameter Dv50 of the positive electrode active material to the average particle diameter Ds of the primary particles is 1.5 to 20; d) the unit lattice parameter a of the positive electrode active material is 0.8200 nm to 0.8250 nm; The electrochemical device according to claim 1 , wherein at least one of the above is satisfied.
7. The unsaturated carbonate compound includes a compound represented by formula (I), 【Chemistry 3】 In formula (I), R 3 is the substituted C 1 -C 6 Alkylene group, substituted or unsubstituted C 2 -C 6 and when substituted, the substituents are selected from halogen atoms, C 1 -C 6 Alkyl group, C 2 -C 6 alkenyl group, and R 3 is replaced by C 1 -C 6 When selected from the alkylene group, the substituents are at least C 2 -C 6 Contains an alkenyl group 2. The electrochemical device of claim 1.
8. The unsaturated carbonate ester compounds are the following compounds (I-1) to (I-8): 【Chemistry 4】 The electrochemical device according to claim 7, wherein the at least one of
9. 2. The electrochemical device according to claim 1, wherein a mass fraction of the unsaturated carbonate ester compound is 0.01% to 5% with respect to a mass of the electrolyte solution.
10. An electric power-using facility comprising the electrochemical device according to any one of claims 1 to 9.
Citation Information
Patent Citations
Doped modified lithium nickel cobalt manganese material, preparation method thereof and lithium ion battery
CN103296249A
Nonaqueous electrolyte secondary battery
JP2003257415A
Nonaqueous electrolyte solution, and lithium secondary battery using nonaqueous electrolyte solution
JP2011034698A
Positive electrode active material and lithium ion battery
JP2021513193A
Positive electrode active material for lithium-ion battery, positive electrode for lithium-ion battery, and lithium-ion battery
WO2011108658A1